Manajemen Air Tanah di DKI Jakarta Berdasarkan Undang-Undang Sumber Daya Air - Talia Sopiyani; Aju Putrijanti (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Indonesia is known as the island nation and is thus viewed as having a large supply of water and water mainly with groundwater. The purpose of this paper is to identify the problem in Jakarta which is the capital of Indonesia, especially in the groundwater management sector. The increased use of groundwater by communities and industries because of its easy process and many benefits, but inadequate groundwater management has resulted in water contamination. Factor causes like air pollution and sewage. Jakarta as the capital of Indonesia has a high level of pollution. The many vehicles and low greenery areas in Jakarta make air pollution poorly handled. Jakarta's society in general works in the industry sector. The amount of industry there with the lack of good groundwater management is the result of industry's waste. As an example in the Muara Angke region in North Jakarta, it is well-known that the fishing industry has a problem with the untreated waste management case. In terms of legislation in Indonesia, especially in the field of water management using the water resources act, act No. 17 of 2019, on water resources which was the result of previous constitutional renewal.Keywords: Management; Groundwater; Water Resources AbstrakIndonesia dikenal sebagai negara kepulauan sehingga dipandang memiliki pasokan air yang banyak terutama dengan air tanah. Tujuan dibuatnya artikel ini untuk mengidentifikasi permasalahan sektor manajemen air tanah di DKI Jakarta serta kebijakan pemerintah dalam pemberian sanksi administratif maupun pidana yang ditinjau dari Undang-Undang Republik Indonesia Nomor 17 Tahun 2019 Tentang Sumber Daya Air. Metode penelitian yang digunakan yaitu yuridis normatif. Banyaknya penggunaan air tanah oleh masyarakat dan industri karena proses yang mudah dan manfaatnya banyak namun manajemen air tanah yang belum maksimal mengakibatkan timbul pencemaran air tanah. Faktor yang disebabkan seperti polusi tanah dan mengakibatkan munculnya limbah padat dan cair. Masyarakat di Jakarta secara umum bekerja di sektor perindustrian. Minimnya manajemen air tanah yang baik mengakibatkan adanya limbah industri. Seperti contoh di daerah muara angke Jakarta Utara yang terkenal dengan wilayah industri perikanan yang memiliki permasalahan manajemen air tanah pada kasus pengolahan limbah terutama limbah cair. Dalam hal legislasi di Indonesia terutama pada bidang manajemen air tanah menggunakan undang-undang sumber daya air yaitu Undang-Undang Nomor 17 Tahun 2019 tentang Sumber daya air.Kata Kunci: Manajemen; Air Tanah; Sumber Daya Air